Ceticismo ético no direito: Problemas conceituais e empíricos do discurso moral - Andre Matos de Almeida Oliveira (2019)
The relation between law and morality is one of the central problems in Philosophy of Lawand in Jurisprudence. Recently, influential authors, such as Dworkin and Alexy, defended astronger integration between both. Our aim in this dissertation, however, is to defend ethicalskepticism in law: i.e. to defend that moral arguments are problematic and should beabandoned. Our skepticism will be based on the claim that two common assumptions aboutmorality are false: that it is objectively valid and that it is (pragmatically) useful. The twoassumptions are connected, but we will analyze them separately. In the first part of thedissertation, we will deal with the first assumption. We will show that we have someintuitions about what morality is - something objective, inescapable, binding, etc., but that,after analysis, these intuitions are not justified. We will conclude by a Moral Error Theory, inthe form presented by the philosopher Richard Joyce. In the second part of the dissertation,we will deal with the second assumption. This assumption is defended by those who say thatalthough moral arguments are not objectively true, they are still useful in the sense that theycan generate consensus and convergences, solve social problems, etc. We will show that thisview is false, at least as far as law is concerned, based on two, more empirical, arguments.The first is that moral arguments tend to create more dissent and social polarization thanconvergences. The second is that moral discussions in law are essentially indeterminate, andthat moral arguments alone will never suffice to solve hard problems exactly those in whichmoral argument would be most needed. Finally, we will confront some objections against ourpositions, as the one that says it is contradictory, put forward by authors such as Dworkin andAlexy; we will reply that these objections are unsuccessful. We will conclude, therefore, byan ethical skepticism in the law.